(untitled) (Research, Society and Development, 2021)
Alternative methods for pain relief aim to make childbirth as natural as possible, reducing unnecessary and harmful interventions, according to the World Health Organization, and rescuing the parturient’s autonomy. The aim of this study was to investigate alternative therapies for the relief of pain from normal delivery in the literature available in different parts of the world. A systematic literature review was carried out in PubMed®, Scientific Electronic Library Online (SciELO), Biblioteca Virtual em Saúde (BVS) and ScienceDirect databases searching for studies published between 2002 and 2019. The research took place between February and April 2020, according to the descriptors “parturition”, “complementary therapies”, “pain” and “normal delivery”. PRISMA recommendations were used and registered in PROSPERO (CRD42020186056). We analyzed 6,758 articles of clinical trial model. A total of 16 articles for qualitative synthesis involving five different countries were included. Most of the studies had primiparous participants, and by inclusion criteria, healthy women, and with usual risk of prenatal care. The 16 studies involved ten different non-pharmacological techniques, with acupuncture and bathing with hot therapy as the most used. Most of the alternative therapies responded satisfactorily in aid of labor pain, besides not being harmful to newborns. The alternative methods in childbirth are comprehensive and collaborative throughout the gestational and parturition process, being statically significant with pain, and providing a range of models that can be planned and employed by maternity hospitals in an easy and economical way.